2017
DOI: 10.3389/fpls.2017.02192
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Perturbs sRNA-Gibberellin Regulatory Network in Immune Response of Potato to Potato virus Y Infection

Abstract: Potato virus Y is the most economically important potato viral pathogen. We aimed at unraveling the roles of small RNAs (sRNAs) in the complex immune signaling network controlling the establishment of tolerant response of potato cv. Désirée to the virus. We constructed a sRNA regulatory network connecting sRNAs and their targets to link sRNA level responses to physiological processes. We discovered an interesting novel sRNAs-gibberellin regulatory circuit being activated as early as 3 days post inoculation (dp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 96 publications
4
41
0
Order By: Relevance
“…The authors inferred that the basal defence and the signals of viral-associated molecular pattern (VAMPs) might play a role in the early stages of miRNA alteration (Bazzini et al 2011). As for the upregulation of miRNAs in the inoculated leaves observed in this study (3 and 6 dpi), it is similar to that observed in Désirée-PVY NTN tolerant response (Križnik et al 2017). The authors demonstrated the downregulation of gibberellin signalling at 3 dpi in the inoculated leaves before viral multiplication could be detected and it might be linked to the reduced disease severity.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The authors inferred that the basal defence and the signals of viral-associated molecular pattern (VAMPs) might play a role in the early stages of miRNA alteration (Bazzini et al 2011). As for the upregulation of miRNAs in the inoculated leaves observed in this study (3 and 6 dpi), it is similar to that observed in Désirée-PVY NTN tolerant response (Križnik et al 2017). The authors demonstrated the downregulation of gibberellin signalling at 3 dpi in the inoculated leaves before viral multiplication could be detected and it might be linked to the reduced disease severity.…”
Section: Discussionsupporting
confidence: 84%
“…Regulation of immune receptor transcripts by miR6022 as well as upregulation of miR164, miR167, miR169, miR171, miR319, miR390 and miR393 in potato cv. Désirée showing tolerant response to PVY NTN revealed similarities to responses observed in mutualistic symbiotic interactions (Križnik et al 2017).…”
Section: Discussionmentioning
confidence: 54%
“…The level of GA was decreased, while the levels of other hormones were not affected. This indicates that, in tolerant response, repression of GA signaling is coupled with an increase in immune receptor gene expression which was corroborated by a discovery of GAMYB binding sites in the MIR6022 promoter region [110].…”
Section: Tolerant Response: Balance Between Plant Defense and Virus Cmentioning
confidence: 64%
“…It was suggested that the early induction of photosynthesis (and other primary metabolism-associated genes) helps to promote the induction of tolerant responses (Figure 2). In the same pathosystem, sRNAs have been shown as an important regulatory level in the establishment of tolerance [110], leveling both, responses in immune signaling and GA regulatory network (Figure 2). Decreased levels of miR6022 were linked with upregulation of its predicted target genes encoding LRR-RLKs, which were shown to be regulated similarly in some mutualistic symbiotic interaction [111].…”
Section: Tolerant Response: Balance Between Plant Defense and Virus Cmentioning
confidence: 99%
“…60-130 sections containing initial virus foci (section A) and surrounding tissue (section B) were sampled from the third inoculated leaf from 6-8 plants of each genotype. Hormones were isolated and measured by gas chromatography coupled with mass spectrometry (GC-MS) as described by Križnik et al, (2017). − Supplemental Figure 12: Spatial transcriptional response is similar in shRBOHD and NahG genotypes.…”
Section: Hormonal Measurementsmentioning
confidence: 99%